2005
DOI: 10.1063/1.1924507
|View full text |Cite
|
Sign up to set email alerts
|

A quantum wave-packet study of intersystem crossing effects in the O(P2,1,3,D21)+H2 reaction

Abstract: We present for the first time an exact quantum study of spin-orbit-induced intersystem crossing effects in the title reaction. The time-dependent wave-packet method, combined with an extended split operator scheme, is used to calculate the fine-structure resolved cross section. The calculation involves four electronic potential-energy surfaces of the 1 AЈ state ͓J. Dobbyn and P. J. Knowles, Faraday Discuss. 110, 247 ͑1998͔͒, the 3 AЈ and the two degenerate 3 AЉ states ͓S. Rogers, D. Wang, A. Kuppermann, and S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 24 publications
6
70
1
Order By: Relevance
“…+ H2, D2, and HD as well as for other systems have been studied with QM scattering methods 4,5 and quasiclassical trajectory surface hopping (TSH) method, 3 of which Han and co-workers 18,21 firstly introduced the benchmark non-adiabatic time-dependent quantum wave packet approach to study non-adiabatic dynamics of chemical reaction. On the theoretical side, Song and Gislason 23 studied the effect of reagent vibration and rotation on the reaction of O+H2 (v = 0, 1, 2; j) using quasiclassical calculations on Johnson-Winter potential energy surface.…”
Section: Introductionmentioning
confidence: 99%
“…+ H2, D2, and HD as well as for other systems have been studied with QM scattering methods 4,5 and quasiclassical trajectory surface hopping (TSH) method, 3 of which Han and co-workers 18,21 firstly introduced the benchmark non-adiabatic time-dependent quantum wave packet approach to study non-adiabatic dynamics of chemical reaction. On the theoretical side, Song and Gislason 23 studied the effect of reagent vibration and rotation on the reaction of O+H2 (v = 0, 1, 2; j) using quasiclassical calculations on Johnson-Winter potential energy surface.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Dobbyn 25−28 In this work, a nonadiabatic quantum dynamics calculation was carried out based on the above PESs to obtain the product branching ratio of OH( 2 Π 3/2 ) to OH( 2 Π 1/2 ), which can be compared directly to experimental measurement. In two previous relevant studies, 27,28 the diabatic representation was used as asymptotic reactants and throughout in the whole calculation to produce the interested dynamical quantities including the product fine-structure ratio. However, the results generated in this way cannot be compared directly with experiment observables.…”
Section: Introductionmentioning
confidence: 99%
“…More recently and related to the title reaction and to the nonadiabatic effects, Chu et al [55] reported an exact quantum wave-packet study of intersystem crossing effects for the O ( 3 P 2,1,0 , 1 D 2 ) + H 2 reaction, in which three triplets,ã 3 A ,b 3 A andã 3 A , and one singlet,X 1 A , electronic states were employed.…”
Section: Quantum Calculationsmentioning
confidence: 99%
“…Most recently, Maiti and Schatz [54] and Chu et al [55] have studied the intersystem crossing effects between the triplet and singlet states. Mainly focused on the O ( 3 P) + H 2 reaction, they found a negligible contribution to this reaction.…”
Section: Characterization Of the O ( 1 D) + H 2 Reactionmentioning
confidence: 99%